Living Jim Crow : the segregated town in mid-century Southern fiction - Lennon, Gavan (Modern American literature and the new twentieth century., 2020)
Analysing the ubiquity of the small town in fiction of the mid-century US South, Living Jim Crow is the first extended scholarly study to explore how authors mobilised this setting as a tool for racial resistance.